Juror Perceptions of Intoxicated Suspects' Interrogation-Related Behaviors. (February 2020) - Mindthoff, Amelia; Evans, Jacqueline R.; Perez, Gissel; Woestehoff, Skye A.; Olaguez, Alma P.; Klemfuss, J. Zoe; Vallano, Jonathan P.; Woody, William Douglas; Normile, Christopher J.; Scherr, Kyle C.; Carlucci, Marianna E.; Carol, Rolando N.; et al.
Alcohol-intoxicated suspects' confessions are admissible in U.S. courts; however, it is unknown how jurors evaluate such confessions. Study 1 assessed potential jurors' perceptions of intoxication in interrogative contexts. Many respondents were unaware that questioning intoxicated suspects and presenting subsequent confessions in court are legal, and respondents generally reported they would rely less on intoxicated than sober confessions. In Study 2, potential jurors read a case about a defendant who had confessed or not while sober or intoxicated. Participants who read about an intoxicated defendant perceived the interrogation as more inappropriate and the defendant as more cognitively impaired than did participants who read about a sober defendant, and as a result, they were less likely to convict. Furthermore, intoxicated confessions influenced conviction decisions to a lesser extent than did sober confessions. Findings suggest that investigators might consider abstaining from interrogating intoxicated suspects or else risk jurors finding confessions unconvincing in court.